Pengaruh Asset Life Cycle Management terhadap Performa Aset Negara - Susanto, Budi; Yudhistira, Muhammad Halley (UI Scholars Hub, 2025)
This study examines the impact of government intervention in asset management systems on the performance of state-owned assets. Using Asset Life Cycle Management (ALCM) indicators and binary logistic regression, the findings reveal that three key aspects of ALCM—strategy and planning, acquisition, and operation and maintenance—significantly influence asset performance. The impact of ALCM policies varies by asset location, categorized into five major regions: Sumatra, Java, Kalimantan, Bali-Nusa Tenggara, and Papua. These results provide empirical evidence that effective asset management policies positively contribute to optimizing the performance of state assets.